A POOLED META-ANALYSIS; THE ROLE OF GENETIC AND ENVIRONMENT ON THE INCIDENCE OF PESTICIDES INTOXICATION ON WORKERS - Ela Laelasari; Haryoto Kusnoputranto; Budiawan Budiawan (Universitas Darussalam Gontor, 2017)
The use of pesticides for pest repellent can trigger the risk of cancer and degenerative diseases for certain groups. The interaction of genetic and environmental (GxE) to be crucial for the case of pesticide intoxication. Knowing the role of genetic factors could be a way of preventing the incidence of intoxication from harmful chemicals pesticides through meta-analysis studies explore the differences between the groups of workers who are at risk with resesive alleles and non-alleles resesive. Statistically significant difference was found in the value of the odds ratio (OR) of 1.6 (CI 0.99-1.02)Keywords: Pesticide; biotransformation; genetic; environment